2005
DOI: 10.1016/j.otohns.2005.05.308
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-S-Transferase Polymorphisms and Risk of Differentiated Thyroid Carcinomas

Abstract: Objective: To determine the association between glutathione S-transferase (GST) polymorphisms and the risk of differentiated thyroid carcinoma (DTC) and benign thyroid tumors.Design: Case-control study.Setting: Tertiary care cancer center. Patients:Two hundred one patients with DTC, 103 patients with benign thyroid tumors, and 680 cancer-free control subjects. Main Outcome Measures:Results of a polymerase chain reaction-based assay for genotyping. A multivariate logistic regression analysis was performed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 8 publications
2
13
0
4
Order By: Relevance
“…The relationship between genotype and phenotype in CYP1A1m1 and CYP1A1m2 is not yet fully understood. Our study also demonstrated that the GSTM1 and GSTT1 null genotypes were distinct between patients and controls, which is consistent with some studies (Morari et al, 2002;Hernández et al, 2003;Gaspar et al, 2004;Bufalo et al, 2006;Ho et al, 2006;Gonçalves et al, 2007;Lemos et al, 2008;Siraj et al, 2008) involving these genotypes and the risk of developin benign and malignant thyroid diseases.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The relationship between genotype and phenotype in CYP1A1m1 and CYP1A1m2 is not yet fully understood. Our study also demonstrated that the GSTM1 and GSTT1 null genotypes were distinct between patients and controls, which is consistent with some studies (Morari et al, 2002;Hernández et al, 2003;Gaspar et al, 2004;Bufalo et al, 2006;Ho et al, 2006;Gonçalves et al, 2007;Lemos et al, 2008;Siraj et al, 2008) involving these genotypes and the risk of developin benign and malignant thyroid diseases.…”
Section: Discussionsupporting
confidence: 93%
“…These protein dimers bind electrophilic molecules and free radicals in order to reduce them to products that are nontoxic to the organism. According to previous studies (Morari et al, 2002;Gaspar et al, 2004;Ho et al, 2006) individuals with the null genotypes for GSTM1 and GSTT1 could have an increased susceptibility to thyroid cancer. In addition, it was suggested that the combination of GSTM1, GSTT1 and GSTP1 polymorphisms promoted a moderate increased risk of thyroid cancer, especially PTC (Siraj et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Polymorphisms of other xenobiotic-metabolizing enzymes such as glutathione S-transferase mu-1 and theta-1 have also been associated with different susceptibilities to thyroid cancer [19][20][21] and this greatly supports the role of xenobiotic-metabolizing enzymes in thyroid carcinogenesis. A role for chemical carcinogenesis in PTC has not yet been established in humans, although animal experiments have identified several compounds with the potential to cause thyroid tumours in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Isso poderia estar confirmando a hipótese do GST ausente ser um fator de melhor prognóstico, pois o GST confere proteção tanto a célula normal como para a neoplásica, e por isso poderia estar relacionado com uma maior agressividade tumoral. No entanto devemos levar em consideração o fato de que o carcinoma papilífero de tireoide apresenta em geral boa evolução clinica, portanto espera-se que haja uma maior frequência de pacientes considerados de baixo risco, independentemente de suas características genéticas 24 . Rigual et al (2005) estudaram 33 pacientes com carcinoma papilífero da tireoide e encontraram uma associação positiva entre a deleção do gene GSTM1 e o risco de recidiva e mortalidade da doença, avaliado pelo sistema GAMES (Memorial Sloan-Kettering) 25 .…”
Section: Métodosunclassified